THE EFFECT OF DIFFERENT PACKAGING MATERIAL ON SEAWEED JAM STORED IN REFRIGERATED TEMPERATURE - Donal '; Dewita Buchari; Suparm ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was aimed to evaluate the effect of various packaging materialon quality changes of seaweed jam strored in refrigerated temperature. Seaweed jamwas prepared from blended seaweed (Eucheuma cottonii) added with sugar, citricacid, and ginger. The jam was packed in glass and plastic bottle and stored atrefrigerated temperature for 30 days. The jam were evaluated for sensory quality,proximate composition and total bacterial count at 0, 10, 20 and 30 days of storage.The results showed that the sensory quality of both seaweed decreased duringstorage; and the seaweed jam stored in glass bottle deereased faster than that stored inplastic bottle. There was no effect of packaging material on moisture, sugar, crudefiber, and total bacterial count. Moisture, sugar, and bacterial count of seaweed jamstored in glass bottle was 32,71%, 58,11%, 1,59% and 11,2 X 104 respectively andstored in plastics bottle was 33,69%, 56,99%, 1,74% and 16,4 X 104 respectively.Keywords : seaweed, Eucheuma cottonii, packaging, storage, refrigerated